PERSEPSI MAHASISWA FAKULTAS HUKUM UNIVERSITAS MULAWARMAN TERHADAP PROGRAM ACARA TALKSHOW “HOTMAN PARIS SHOW” DI INEWS TV - Abdul Rahman; Nurliah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
I-News TV has started to include entertainment and talkshows in its programs, one of which is the Hotman Paris Show. The Hotman Paris Show program continues to be broadcast on television in several episodes which are controversial or prohibited. The impact of the figure of Hotman Paris is reflected in the motivation that creates perceptions among Law Faculty students. One of the things that went viral was the perception of new students at the University of North Sumatra, Medan, because they saw the Hotman Paris Show program as one of the reasons for entering the Faculty of Law. This study aims to find out the perceptions of students of the Faculty of Law, University of Mulawarman towards the